Socio-cultural factors associated with the uptake of human papilloma virus vaccine among girls aged 9-13 years in Garissa County, Kenya - Hussein, Risala; Gitonga, Eliphas; Wambugu, Monica (International Journal Of Community Medicine And Public Health, 2025)
Background: Cervical cancer remains a major health concern, driven mainly by human papilloma virus (HPV) types 16 and 18. In Kenya, it is the second most common cancer, yet HPV vaccination coverage is still low, with Garissa County at only 2%. Cultural norms, hesitancy, and limited awareness hinder uptake. This study assesses socio-cultural factors shaping vaccination to guide improved interventions. Methods: The study employed a descriptive cross-sectional design. Using systematic sampling, 437 respondents were recruited from public primary schools. Data were collected via questionnaires with informed consent/assent. Ethical approval was obtained from KUERC, and permits from NACOSTI. Statistical package for the social sciences (SPSS) v26.0 was used for descriptive and Chi-square analyses at a 95% confidence level, with results presented in tables and charts. Results: The study found HPV vaccine uptake at 5.7% among girls aged 9–13 years in Garissa County. Most guardians were aged 29–38 years, 92.2% Muslim, and 50.8% had no formal education. Further result revealed key factors reducing uptake includes beliefs that the vaccine causes infertility (p=0.002), myths about its effectiveness (p=0.036), fear of side effects (p=0.001), and perceptions that it encourages promiscuity (p=0.001). Conclusions: HPV vaccine uptake among girls was very low (94.3% unvaccinated). Non-uptake was linked to beliefs about infertility, myths on efficacy, fear of side effects, and concerns about promoting promiscuity. The study recommends targeted education, engagement with religious and cultural leaders, public awareness campaigns, assured vaccine availability, and integration of HPV vaccination into routine services to improve acceptance and reduce the cervical cancer burden.